Relationship between Interpersonal Sensitivity Measure score and clinical symptoms in patients with major psychiatric disorders and healthy individuals. Issue 2 (15th June 2022) - Hidese, Shinsuke; Matsuo, Junko; Ishida, Ikki; Yokota, Yuuki; Ota, Miho; Hattori, Kotaro; Kunugi, Hiroshi
Abstract: Aim: We compared the Interpersonal Sensitivity Measure (IPSM) scores between diagnostic groups and examined the relationship between IPSM scores and clinical variables. Methods: This study included 166 patients with schizophrenia, 47 patients with bipolar disorder (BD) Ⅰ, 110 patients with BD Ⅱ, 380 patients with major depressive disorder (MDD), and 558 healthy individuals. Symptoms were assessed using the Positive and Negative Syndrome Scale (PANSS), Young Mania Rating Scale, 21‐item Hamilton Depression Rating Scale (HAMD‐21), and Pittsburgh Sleep Quality Index (PSQI). Results: The IPSM interpersonal awareness, separation anxiety, timidity, fragile inner self, and total scores were significantly higher in all the patient groups compared with healthy individuals (corrected p  < 0.05). The IPSM need for approval score was significantly higher in patients with BD Ⅰ and those with BD Ⅱ than in those with schizophrenia or MDD (corrected p  < 0.05). The PSQI total score and PANSS general psychopathology score, HAMD‐21 delusion subscale score, HAMD‐21 total score, and HAMD‐21 core subscale score and PSQI sleep disturbance subscale score were significantly and positively correlated with the IPSM total score in patients with schizophrenia, those with BD Ⅰ, those with BD Ⅱ, and those with MDD, respectively, while the PSQI total score and daytime dysfunction subscale score were significantly and positively correlated with the IPSM total score in healthy individuals (corrected p  < 0.05). Conclusion: Our data suggest that higher interpersonal sensitivity may play a role in the development of major psychiatric disorders and may be involved in some clinical symptom formations.